(untitled) (Journal of Plant Disease Sciences, 2025)
Chickpea is one of the most important pulse crops, contributing a lion’s share to the world’s gram production. Fusarium wilt is a serious soil-borne disease that affects chickpea productivity. Biological control using native Plant Growth Promoting Rhizobacteria (PGPR) isolated from rhizosphere soils offers a sustainable and eco-friendly solution for managing this disease. These PGPR also enhance plant growth by increasing nutrient uptake, siderophore production, and the synthesis and release of growth-promoting hormones.The present study was conducted to isolate and identify potential native PGPR species from the Marathwada region of Maharashtra for the dual purpose of managing Fusarium wilt and promoting chickpea growth. A total of 19 rhizosphere soil samples were collected from healthy chickpea fields across three agro-climatic zones of the region.Among the isolates, species coded as CPP produced medium-sized, white, convex, smooth, regular colonies with yellowish-green pigmentation, gram-negative reaction, rod-shaped cells, and negative sporulation. In contrast, species coded as CSN, CSB, and CSO formed small-sized, white, convex, smooth colonies with irregular to regular margins, light green pigmentation, gram-negative reaction, rod-shaped cells, and negative sporulation.